Toxic effects of Cr(VI) on the bovine hemoglobin and human vascular endothelial cells: Molecular interaction and cell damage. (May 2019) - Cao, Xiangyu; Wang, Shuai; Bi, Ruochen; Tian, Siqi; Huo, Yapeng; Liu, Jianli
Abstract: Hexavalent chromium [Cr(VI)] is the main harmful component in the atmosphere released by chemical industry. The study was conducted to assess Cr(VI) inducing cardiovascular diseases (CVDs) in vitro by investigating the effects of Cr(VI) on bovine hemoglobin (BHb) and human umbilical vein endothelial cells (HUVECs). Multi-spectroscopic techniques and molecular docking method were used to determine the interaction of Cr(VI) and BHb. Fluorescence spectra results showed that the quenching constant (Ksv ) decreased with temperature raise, indicating that Cr(VI) quenches BHb fluorescence through static quenching mechanism. The number of binding sites was 1.14 (310 K), enthalpy and entropy changes revealed the interaction of Cr(VI) and BHb was driven by hydrogen bonds. The results of synchronous fluorescence and circular dichroism (CD) spectra suggested that Cr(VI) could change BHb conformation and influence the microenvironment of Trp and Tyr residues. Moreover, in order to study Cr(VI) induced HUVECs damage, inflammatory factors were detected at the mRNA level, JNK and p38 MAPK pathways were analyzed. The results shown that Cr(VI) could induce mRNA expression of NLRP3, ICAM-1, VCAM-1, TNF-α and IL-1β, and increased intracellular ROS. Furthermore, Cr(VI) could induce oxidative stress in HUVECs, and then activate JNK and p38 MAPK pathways, ultimately lead to apoptosis of HUVECs by activating mitochondrial apoptosis pathways. These results suggested that Cr(VI) might bring about CVDs by both changing the BHb conformation and inducing HUVECs damage. Graphical abstract: The interaction between BHb and Cr(VI) primarily were hydrogen bond, and the quenching mechanism of them was static quenching. Cr(VI) had quenching effect on Trp residue and Tyr residue, and changed the secondary structure of BHb. Cr(VI) also induced apoptosis and oxidative stress of vascular endothelial cell via regulating p38 MAPK and JNK pathways.Image 1 Highlights: The interactions between Cr(VI) and Bovine hemoglobin (BHb) have been investigated. The conformational changes indicate that Cr(VI) induces damage of BHb. Cr(VI) induces human umbilical vein endothelial cells (HUVECs) apoptosis in vitro. Cr(VI) up-regulates the expression of inflammation gene in HUVECs. Cr(VI) induces oxidative stress in HUVECs through activation of ROS.